The Effect of The “DEMASI” Method on The Ability of Self Evacuation on Landslide Disaster - Pria Wahyu Romadhon Girianto (International Journal of Health and Medicine, 2025)
A landslide disaster is a life-threatening event that can result in loss of life, environmental damage, and property loss, so it is necessary to have self-evacuation capabilities. Self-evacuation capabilities can be improved with the DEMASI method (Video Animation and Simulation). The aim of this research is to determine the effect of DEMASI (Video Animation and Simulation) on the ability to self-evacuate landslides in class X students at SMA Negeri 1 Dongko. Pre-experimental design research design with a one-group pretest-posttest approach without control. The purposive sampling technique obtained 34 respondents from 170 populations. The research instrument used an observation sheet on self-evacuation capabilities for landslide disasters. Wilcoxon Signed Rank Test statistical test with α 0.05. The results of the research before being given DEMASI intervention (Video Animation and Simulation) were that all (100%) respondents had poor abilities, and after the intervention almost all (85.3%) respondents had good abilities. Results: The statistical analysis showed that the p-value was 0.000 < α 0.05, so there was an influence of DEMASI (Video Animation and Simulation) on students' self-evacuation ability for landslide disasters. The DEMASI method (Video Animation and Simulation) combines two methods that are more interesting, effective, and interactive because audiovisuals recorded by optic and auditory nerves are sent to the occipital lobe and temporal lobe to be described and processed, which involves many brain regions and the frontal lobe so that they can influence the respondent's abilities. The DEMASI method can be used as an educational medium for students and other school residents in an effort to improve their ability to self-evacuate in landslide disasters.